Textocracy, or, the cybernetic logic of French theory. (February 2020) - Geoghegan, Bernard Dionysius
This article situates the emergence of cybernetic concepts in postwar French thought within a longer history of struggles surrounding the technocratic reform of French universities, including Marcel Mauss's failed efforts to establish a large-scale centre for social-scientific research with support from the Rockefeller Foundation, the intellectual and administrative endeavours of Claude Lévi-Strauss during the 1940s and 1950s, and the rise of communications research in connection with the Centre d'Études des Communications de Masse (CECMAS). Although semioticians and poststructuralists used cybernetic discourse critically and ironically, I argue that their embrace of a 'textocratic' perspective – that is, a theory of power and epistemology as tied to technical inscription – sustained elements of the technocratic reasoning dating back to these 1920s efforts to reform French universities.